The Practicality of the Problem Based Learning (PBL) with the Integration Pattern of Science, Technology, and Society (STS) Education for Grade 4 Elementary School Students - Fajar Setiawan; Siti Masitoh; Andi Mariono (Universitas Sultan Ageng Tirtayasa, 2022)
This study aimed to describe the practicality of the Problem-based Learning (PBL) with the integration pattern of Science, Technology, and Society (STS) education for fourth-grade elementary school students. In this study, the development research model was used, referring to Borg and Gall's, a process carried out to produce and test an educational product. The results of the study showed (1) the total mean implementation of the PBL-STS model obtained a score of 1.7 and was declared implemented based on the implementation criteria of the PBL-STS model; (2) The total percentage of learning implementation obtained a value of 89.1% and was declared good based on the learning implementation criteria; and (3) the total percentage of student activity obtained a value of 86.3% and was declared good based on student activity criteria. Based on these results, it can be concluded that the PBL-STS Model is practical for fourth-grade elementary school students.